EXPLORING THE IMPACT OF TRANSFORMATIONAL LEADERSHIP ON WORK PRODUCTIVITY DYNAMICS AT PT MITSUBISHI ELECTRIC AUTOMOTIVE INDONESIA - Joko Dwiarto; Agung Surya Dwianto (PT. Jurnal Center Indonesia Publisher, 2025)
This study aims to explore the impact of transformational leadership on work productivity dynamics at PT Mitsubishi Electric Automotive Indonesia. Transformational leadership, which emphasizes inspiration, intellectual stimulation, individualized consideration, and value-based motivation, is thought to have a significant influence on improving employee productivity. However, how such mechanisms work in the context of the automotive industry in Indonesia still requires in-depth exploration. Using a qualitative approach, this research adopts a case study method to analyse the perceptions, experiences, and interactions of employees and managers in responding to transformational leadership styles. Data was collected through in-depth interviews with managers and employees at PT Mitsubishi Electric Automotive Indonesia, as well as participatory observation in the work environment. Thematic analysis was used to identify key patterns related to motivation, work engagement, and productive behaviour change. The results revealed that transformational leadership contributes to increased productivity through three main mechanisms: (1) strengthening the psychological climate that encourages innovation, (2) increasing organizational commitment through identification with the company's vision, and (3) optimizing team collaboration through inspiring communication. However, implementation challenges were also identified, including resistance to change and a gap between management expectations and employees' adaptive capacity. The implications of this study provide practical insights for companies in designing more effective leadership development programs, while enriching the human resource management literature with a contextual perspective from the Indonesian automotive industry. Policy recommendations include case-based leadership training, participatory feedback approaches, and integration of transformational values in corporate culture.